2011
DOI: 10.1177/0954407011408649
|View full text |Cite
|
Sign up to set email alerts
|

Advanced modern low-emission two-stroke cycle engines

Abstract: This paper reviews recent engines and associated technology offering potential lowemission two-stroke cycle operation for a range of applications. The study considers and discusses successfully applied modern production engines together with concepts exploring advanced possibilities for future application. The published results from research and development projects and the data from available technology are compared in terms of the specific performance. The paper does not compare combustion strategies or flui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 41 publications
2
21
0
Order By: Relevance
“…The work presented here has demonstrated potential for a power plant solution offering low emissions whilst retaining a low production cost base. The stepped piston engine has demonstrated low NOx emission for a motorcycle operating on the LA4 test cycle as reported by Hooper et al [12]. The low NOx emissions modelled in this study offer significant potential to contain this most challenging emission.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The work presented here has demonstrated potential for a power plant solution offering low emissions whilst retaining a low production cost base. The stepped piston engine has demonstrated low NOx emission for a motorcycle operating on the LA4 test cycle as reported by Hooper et al [12]. The low NOx emissions modelled in this study offer significant potential to contain this most challenging emission.…”
Section: Discussionsupporting
confidence: 72%
“…Experimental testing from prototype stepped piston engines [12][16] [17] has shown that the power density of the engine type lies between the conventional four-stroke and two-stroke cycle engine levels. The relative size of current stepped piston engines is similarly between the two fundamental engine types as can be seen in The engines shown in Fig 3 are compared in terms of identical cylinder swept volumes.…”
Section: Stepped Piston Enginesmentioning
confidence: 99%
See 1 more Smart Citation
“…Such technology is not uncommon on modern two stroke engines for automotive or marine applications; however this does present an additional challenge to the UAV system designers. The complication can be avoided by using more advanced UAV two-stroke cycle engines such as segregated scavenging engines as discussed by Stone (2012) and Hooper et al (2011Hooper et al ( , 2012. In these forms of two stroke engines the lubrication system and air delivery systems are separated from each other and the oil circulation system forms an integral part of the engine design in a similar method achieved by four stroke engines with re-circulatory lubricant flow control.…”
Section: Discussionmentioning
confidence: 99%
“…For UAVs this has stimulated research and development of engines to meet this requirement using a range of approaches employing adapted conventional two stroke engines as demonstrated by the work of Duddy et al (2011), Hooper and Hooper (1996), Blank et al (2001) and Cathcart et al (2006). Alternative engine design methodologies have also been developed using novel techniques as discussed by Stone (2012), Hooper and Hooper (1996), Hooper (2001Hooper ( , 2005 and Hooper et al (2011Hooper et al ( , 2012. Opposed piston designs have been proposed by Kalkstein et al (2006) and there have been cases considering four stroke engines as presented by Cathcart et al (2005).…”
Section: Introductionmentioning
confidence: 99%